The Prostaglandin E2-EP3 Receptor Axis Regulates Anaplasma phagocytophilum-Mediated NLRC4 Inflammasome Activation - Wang, Xiaowei; Shaw, Dana K; Hammond, Holly L; Sutterwala, Fayyaz S; Rayamajhi, Manira; Shirey, Kari Ann; Perkins, Darren J; Bonventre, Joseph V; Velayutham, Thangam S; Evans, Sean M; Rodino, Kyle G; VieBrock, Lauren; et al. (PLoS pathogens, 2016)
Rickettsial agents are sensed by pattern recognition receptors but lack pathogen-associated molecular patterns commonly observed in facultative intracellular bacteria. Due to these molecular features, the order Rickettsiales can be used to uncover broader principles of bacterial immunity. Here, we used the bacterium Anaplasma phagocytophilum, the agent of human granulocytic anaplasmosis, to reveal a novel microbial surveillance system. Mechanistically, we discovered that upon A. phagocytophilum infection, cytosolic phospholipase A2 cleaves arachidonic acid from phospholipids, which is converted to the eicosanoid prostaglandin E2 (PGE2) via cyclooxygenase 2 (COX2) and the membrane associated prostaglandin E synthase-1 (mPGES-1). PGE2-EP3 receptor signaling leads to activation of the NLRC4 inflammasome and secretion of interleukin (IL)-1β and IL-18. Importantly, the receptor-interacting serine/threonine-protein kinase 2 (RIPK2) was identified as a major regulator of the immune response against A. phagocytophilum. Accordingly, mice lacking COX2 were more susceptible to A. phagocytophilum, had a defect in IL-18 secretion and exhibited splenomegaly and damage to the splenic architecture. Remarkably, Salmonella-induced NLRC4 inflammasome activation was not affected by either chemical inhibition or genetic ablation of genes associated with PGE2 biosynthesis and signaling. This divergence in immune circuitry was due to reduced levels of the PGE2-EP3 receptor during Salmonella infection when compared to A. phagocytophilum. Collectively, we reveal the existence of a functionally distinct NLRC4 inflammasome illustrated by the rickettsial agent A. phagocytophilum.
Keywords: Ehrlichiosis; Inflammasomes; Receptors, Prostaglandin E, EP3 Subtype; Real-Time Polymerase Chain Reaction; receptory prostaglandinů E - podtyp EP3; imunoblotting; Disease Models, Animal; myši inbrední C57BL; proteiny vázající vápník; Mice; myši knockoutované; kvantitativní polymerázová řetězová reakce; Immunoblotting; modely nemocí na zvířatech; ELISA; zvířata; Apoptosis Regulatory Proteins; Anaplasma phagocytophilum; ehrlichióza; Dinoprostone; Mice, Knockout; Calcium-Binding Proteins; inflamasomy; myši; proteiny regulující apoptózu; Enzyme-Linked Immunosorbent Assay; dinoproston; Mice, Inbred C57BL; Animals